THU0031 High synovial fluid and serum il-18 levels in patients with rheumatoid and psoriatic arthritis. (1st June 2001) - Pittoni, V; Bombardieri, M; Spadaro, A; Ossandon, A; Spinelli, FR; Taccari, E; Riccieri, V; Rinaldi, T; Alessandri, C; Valesini, G
Abstract : Background: IL-18 is a recently identified cytokine with a broad array of proinflammatory actions. Il-18 is expressed at sites of chronic inflammation in human autoimmune diseases and is thought to play a pathogenetic role especially in those immune-mediated diseases with a predominant Th1 cytokine profile. Objectives: The aim of this study was to measure IL-18 levels in sera and synovial fluids (SF) of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and osteoarthritis (OA). Methods: Eighty-one patients were studied, of which thirty-three with RA (11M, 22F; mean age 54.7 ± 12.8 yrs), twenty-nine with PsA (23M, 6F; mean age 48.1 ± 14.2 yrs) and nineteen with OA (9M, 10F; mean age 63.6 ± 8.8 yrs). After centrifugation sera and SF were stored at -20°C and a sandwich enzyme-linked IL-18 immunoassay was performed. Statistical analysis was carried out using non parametric methods. Results: IL-18 levels were significantly higher in SF than in sera of either RA (mean value ± SD = 6, 758 ± 3, 702 pg/ml vs 575 ± 1, 118 pg/ml, p = <1 × 10 –6 ), PsA (4, 234 ± 2, 834 pg/ml vs 556 ± 634 pg/ml, p = <1 × 10 –5 ) and OA patients (1, 054 ± 1, 215 pg/ml vs 283 ± 542 pg/ml, p = 0, 002). Serum IL-18 levels were significantly higher in RA(p < 0.05) and in PsA (p < 0.01) than in OA, while no significant difference between RA and PsA serum levels was found. SF IL-18 levels were significantly more increased in RA than in PsA (p < 0.01) and OA (p < 1 × 10 –8 ). SF IL-18 levels in PsA were also higher than in OA (p < 0.0002). Conclusion: This study indicates that IL-18 levels are augmented in immune-mediated inflammatory arthropaties such as RA and PsA as against OA where degenerative mechanisms are generally associated with mild inflammation. The difference found is more striking if SF rather than sera were considered. The increased concentration of IL-18 found in SF as against sera in the three groups of patients suggests a pivotal role of this cytokine in local mechanisms of inflammation.